CONSTRUCTING DIPLOMATIC IDENTITY: A MORPHO-PRAGMATIC ANALYSIS OF DERIVATIONS IN PRABOWO'S UN SPEECH - Dio Fathan; Giacinta Azzahra; Yanti Rosalinah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study examines the role of derivational morphology in shaping diplomatic identity in President Prabowo Subianto’s speech at the 80th United Nations General Debate. Despite extensive analysis of political discourse, the pragmatic function of derivational processes in diplomatic communication is still barely investigated. The study addresses this gap by identifying the types and communicative functions of derivational morphemes utilized in speech, elucidating how these forms facilitate Indonesia's diplomatic self-presentation. The research employs a descriptive qualitative methodology to evaluate the official transcript by Fairclough’s Critical Discourse Analysis, concentrating on representation, identity formation, and ideological positioning. The research identified 117 derivational forms, including nominalizations, adjectival derivatives, verbalizations, and prefixations. Nominal derivatives like humanity, prosperity, and equality conceptualize political issues as universal ethical ideals, but adjectival forms such as international, multilateral, and democratic situate Indonesia within global institutional standards. Verbal derivatives such as